UNRAVELING GENETIC DIVERSITY THROUGH MOLECULAR INSIGHTS: RAPD PROFILING OF HYBANTHUS ENNEASPERMUS (L.) F. MUELL. - T. C. Beaula Stary1, S. Uma Devi2, Beena Lawrence3 and G. Johnsi Christobel4., (Chelonian Research Foundation, 2024)
Hybanthus enneaspermus (L.) F. Muell, commonly known as the Indian Violets or Purple Balsam, is a flowering plant belonging to the family Violaceae. It is widely distributed in tropical and subtropical regions. It holds cultural and medicinal importance in various traditional systems of medicine. Extracts from different parts of the plant have been traditionally employed to address ailments ranging from respiratory conditions to skin disorders. RAPD (Random Amplified Polymorphic DNA) analysis is a molecular biology technique used to generate fingerprint-like patterns of genomic DNA. In this study, we employ RAPD analysis to investigate the genetic diversity and relationships within species/Population/group of interest. Through the amplification of random genomic regions, we aim to generate informative banding patterns that will serve as molecular fingerprints for the individuals under investigation. This study clearly demonstrates the efficacy of this technique as a robust tool for molecular characterization, underscoring its relevance in contemporary genetic research. Key Words: Hybanthus enneaspermus, Electrophoresis, Genetic diversity, RAPD.